Local Air and Soil Temperature Modeling Using Himawari 8 Satellite Imagery - Adhia Azhar Fauzan; Komariah Komariah; Sumani Sumani; Dwi Priyo Ariyanto; Tuban Wiyoso (Universitas Sebelas Maret, 2018)
Himawari 8 satellite image, which was launched in October 2014 and began the operational in July 2015, serves to identify and track the phenomenon of rapid changes in weather. The purpose of this research was to determine the model of local air and soil temperatures using Himawari 8 satellite image. Local air and soil temperatures information was collected from the Climatology Station of Semarang district, Central Java, Indonesia. Interpretation of the Himawari 8 satellite image was performed, as well as the statistical tests of correlation and regression, according to the sun's pseudo motion. Pair correlation and regression analysis on satellite image with air temperature; and air temperature with soil temperature (bare and grass). The results showed the satellite imagery of Himawari 8 could predict the air and soil temperatures, especially bare soil. In specific, the accuracies were higher on soil temperature at 0 (surface) and 5 cm depth. But each period produced vary accuracy, due to many weather elements had may affect the air and soil temperatures.